(untitled) (Castilla. Estudios de Literatura, 2012)
Whereas in its origins and during a long time poetry was linked to oral and popular culture, nowadays poetry has become a written literary genre that generally is addressed to a minority and selected audience. Nevertheless, in the last years, a very striking phenomenon is happening: the emergence of new genres of oral poetry, addressed to a wider audience. In this paper, it is intended to introduce briefly these new literary expressions and explore one of the genres with more success within the new oral poetry: poetry slam.